FRI0362 Pronostic Factors of Survival in ANCA-Associated Vasculitis (AAV). Changes in The New Century. (15th July 2016) - Rodriguez-Carballeira, M.; Fraile, G.; Martinez-valle, F.; Saez, L.; Rios, J.J.; Solanich, X.; Pasquau, F.; Fonseca, E.; Zamora, M.; Calleja, J.L.; Oristrell, J.; Frutos, B.; et al.
Abstract : Background: AAV are still related to a high morbidity and mortality in spite of new available therapies. To recognize factors associated with a worse prognosis is essential to tailor the treatment Objectives: To identify survival prognostic factors in a large cohort of patients with AAV from Spain and analyze changes in the new century Methods: multicenter retrospective-longitudinal study that included patients diagnosed with AAV between Jan95 and Nov14 in 20 Hospitals from Spain (REVAS Study). Statistical analysis was done using SPSS vs21 Results: 455 patients were included: 188 (41.3%) GPA, 167 (36.7%) MPA, 100 (22%) EGPA. Mean age at diagnosis was 55.7±17.2 y. ANCA were positive in 86.8% of cases:35.8% C-ANCA and 51% P-ANCA. Median time to diagnosis was 4 weeks (IQR 10). Median follow-up was 80 months (IQR 105). Renal, lung, neurological and cardiac involvement were present in 56.7, 54.7%, 34.5% and 12.7% of cases, respectively. Pulmonary-renal syndrome was observed in 17%, ENT in 44.8% and eye involvement in 13.4%. Mean BVAS at diagnosis was 17.7±7.7. All patients received oral glucocorticoids; 342 (75%) cyclophosphamide (50.3% oral), and 6.6% biological therapy. Dialysis was required in 16.4% of cases and plasma exchange in 7%. During follow-up, 22.2% of patients suffered leucopenia, 39% bacterial infections, 12.7% opportunistic infections and 5.3% neoplasms. One hundred thirty (28.6%) patients died: 74 (44.3%) with PAM, 42 (22.3%) with GPA and 14 (14%) with EGPA (p<0.001). Median time to death was 57.5 months (IQR 105): significantly higher for EGPA (94m vs 69m for GPA and 50m for PAM;LogRank=0.01). Comparing diagnostic century, the percentage of deaths was higher in the XXth than in XXIth (48% vs 21%, p<0.001). No differences were found in clinical manifestations, but yes in treatment and rate of infections: in the actual century more plasma exchange is used (9% vs 2.2%, p=0.008), more biological therapy (9% vs 0.7%, p<0.001), less oral CF (29% vs 57.8%, p<0.001) and more CF IV pulses (52% vs 35.6%, p=0.001). Multifactorial Cox regression analysis showed that prognostic factors associated with survival were age>65y (HR 4.6), cardiac (HR 3.9) and renal involvement (HR 2.0). ENT involvement was a protector factor (HR 0.4). Bacterial infections during follow-up were also independent predictor of poor prognosis (HR 2.0) Conclusions: survival rate in AAV has significantly improved in the new century probably due to new treatment strategies, including less CF and biological therapy. Poor prognostic factors are age>65y, cardiac and renal involvement at diagnosis, and bacterial infections, while ENT involvement is protective. Disclosure of Interest: None declared